A study of frequency of occurrence and severity of thrombocytopenia in malaria in 2 months to 18-year-old children in a tertiary care centre at rural Haryana - Narayan, Raghvendra; Singh, Shivani (Indian Journal of Child Health, 2017)
Objective: To study the frequency and severity of thrombocytopenia in children between age groups of 2 months and 18 years with malaria. Materials and Methods: It was a prospective study conducted at tertiary care centre of rural Haryana. Data of confirmed cases of malaria with regard to age, sex, and platelet count were recorded in pre-defined pro forma. Results: Out of total 79 confirmed cases of malaria, 67 (84.81%) cases of Plasmodium vivax, 10 (12.65%) cases of Plasmodium falciparum, and 2 (2.53%) cases of mixed type were observed. Total 58 (73.41%) cases had thrombocytopenia. A total of 50 (74.62%) and 6 (60%) cases had thrombocytopenia in P. vivax and P. falciparum, respectively. Total 17 patients (P. vivax - 14, P. falciparum - 2, and mixed - 1) had severe thrombocytopenia (platelet count